The Legal Protection for Officials Making Land Deeds for Making Deeds of Sale and Purchase of Land that Causes Disputes - Alfian, Danang; Hafidz, Jawade (Jurnal Konstatering, 2023)
This study aims to analyze: 1) Responsibilities of Land Deed Officials (PPAT) for making land sale and purchase deeds that cause disputes. 2) Legal protection for Land Deed Making Officials (PPAT) for making land sale and purchase deeds that give rise to disputes. The approach method in this research is a sociological juridical approach. The specification of the research used is descriptive analytical research. Types of data using primary and secondary data. Data collection by interview method and literature study. The data analysis method used is qualitative analysis. The results of the study concluded: 1) The responsibility of the Land Deed Making Officer (PPAT) in making land sale and purchase deeds that give rise to disputes is as a witness, 2) Legal protection for the Land Deed Making Officer (PPAT) for making land sale and purchase deeds that give rise to disputes is that the PPAT can ask IPPAT for legal protection/defense efforts. PPATs who are summoned as witnesses can ask for help from professional organizations of IPPAT to get assistance during examinations and even at the central level. The legal assistance provided by IPPAT applies to PPATs who are not proven guilty. Based on the theory of legal protection, the provisions regarding the legal protection of the Official for Making Land Deeds are not regulated normatively in the Position Regulations for the Official for Making Land Deeds. Repressive legal protection for PPATs related to making Deeds that give rise to disputes can be achieved by using the right of denial. Keywords: Disputes; Protection; Purchase; Sale.